Effects of age and insulin‐like growth factor‐1 on rat neurotrophin receptor expression after nerve injury. Issue 4 (3rd August 2016) - Luo, T. David; Alton, Timothy B.; Apel, Peter J.; Cai, Jiaozhong; Barnwell, Jonathan C.; Sonntag, William E.; Smith, Thomas L.; Li, Zhongyu
ABSTRACT: Introduction: Neurotrophin receptors, such as p75 NTR, direct neuronal response to injury. Insulin‐like growth factor‐1 receptor (IGF‐1R) mediates the increase in p75 NTR during aging. The aim of this study was to examine the effect of aging and insulin‐like growth factor‐1 (IGF‐1) treatment on recovery after peripheral nerve injury. Methods: Young and aged rats underwent tibial nerve transection with either local saline or IGF‐1 treatment. Neurotrophin receptor mRNA and protein expression were quantified. Results: Aged rats expressed elevated baseline IGF‐1R (34% higher, P  = 0.01) and p75 NTR (68% higher, P  < 0.01) compared with young rats. Post‐injury, aged animals expressed significantly higher p75 NTR levels (68.5% above baseline at 4 weeks). IGF‐1 treatment suppressed p75 NTR gene expression at 4 weeks (17.2% above baseline, P  = 0.002) post‐injury. Conclusions: Local IGF‐1 treatment reverses age‐related declines in recovery after peripheral nerve injuries by suppressing p75 NTR upregulation and pro‐apoptotic complexes. IGF‐1 may be considered a viable adjuvant therapy to current treatment modalities. Muscle Nerve 54 : 769–775, 2016